OSCE in early 21st century: The place, role and scope - Aćimović Ljubivoje (Međunarodni Problemi)
The author firstly deals with the genesis and evolution of the Organization for Security and Co-operation in Europe comparing the basic characteristics of OSCE with those of the previous CSCE. Then follows an analytical survey of the CSCE/OSCE activities in the 1990s, which are grouped into the following three fields: institutional build-up of the Organization, normative and programmatic activity as well as the operational and implementation activity. The author makes an analysis of the Charter for European Security adopted at 1999 OSCE Istanbul summit. The final part projects what further development and role of OSCE is likely to be in the field of security and co-operation in the Euro-Atlantic region, pointing out that in the foreseeable period OSCE will probably mainly retain its present role, significance and the structure of activities, unless some unexpected events occur in the sphere of international affairs. [Objavljujemo posthumno poslednji rad dr Ljubivoja Aćimovića, naučnog savetnika u Institutu za međunarodnu politiku i privredu, koji je provobitno publikovan u našem časopisu u broju 3, 2000. godine. Naš kolega je preminuo 1. januara 2013. godine.]